Optimization of Lip Balm Formula From Buni Fruit Extract (Antidesma bunius L. Spreng) with A Combination of Beeswax Lanolin - Syahputri, Acyuta Pramesthi Asmara Sayidina; Hajrin, Wahida; Subaidah, Windah Anugrah (Jurnal Biologi Tropis, 2025)
Lip balm is a preparation with a wax base that is applied to the lips to moisturize them so they aren’t easily dry and cracked. Lip balm, when used, is very dependent on its adhesive power and spreadability, which are influenced by the composition of the base and the additional ingredients. The purpose of this study was to determine the optimum concentration of beeswax and lanolin in Lip balm preparations as wax and softening agents using the Simplex Lattice Design (SLD) method. Extraction of buni fruit was carried out by the maceration method using 80% ethanol solvent and 3% citric acid (85: 15). Data analysis was carried out using ANOVA to see the distribution of data on parameters of physical properties, and a one-sample T-test for confirmation analysis of the optimum formula composition. The results of the study obtained an extract yield of 41.534% and positively contained anthocyanins. The analysis results of physical properties using Design Expert v.13, the optimum concentration of beeswax was 12% and lanolin 4% with a desirability value is 1. The Lip balm with buni fruit extract, with the optimum formula, had a dense, homogeneous texture, brownish red with a peach aroma, and a pH of 4. Verification of the optimum formula showed no significant difference between the experimental response and the predicted response, with a value of melting point 53±1 oC; adhesive power 24.42±3.55 seconds; spread power 3.226±0.031 cm. The optimum formula produced physical properties that meet the specified requirements, and the verification results showed a match between the predicted response and the experimental results.